The Cost of Irrigation Water in the Jordan Valley - van den Berg, Caroline; Al Nimer, Sana Kh. H. Agha (World Bank, Washington, DC, 2016)
The purpose of this study was to determine the financial cost of irrigation water in the Jordan Valley and the corresponding impact of higher water prices on farming. The analysis shows that JVA needs significant tariff increases to be able to attain a more financially sustainable footing. In case JVA wants to at least cover its operating and maintenance costs in 2013, it will require JD 0.108 per m3 - assuming that the current cross-subsidies and current inefficiency levels remain unchanged. Yet, if the JVA would be able to reduce its billing and collection inefficiencies, the required irrigation water tariff drops to JD 0.066 per m3. The more efficient JVA becomes in providing irrigation water, the smaller the required tariff increases. The JVA can improve its efficiency by (i) changing billing and collection practices; (ii) change in the revenue policies; and (iii) efficiency gains in the delivery of JVA services. The impact of tariff increases on farmers’ incomes is in general very moderate because water costs make up only a small part of the total cost of farming. Certain cropping patterns will be much more affected by the tariff increases than others. It is especially crops that tend to consume large volumes of water (citrus), that will feel the impact of the irrigation water tariffs. Because the agricultural sector in Jordan is under stress, any government policy to rationalize irrigation water subsidies should where possible try to increase the resilience of farmers. The farmer survey found that 17 percent of the survey respondents could be classified as poor for which specific measures may be needed to help them cope with the effect of higher water prices.